2020
DOI: 10.1093/ilar/ilab012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Management of Gastrointestinal Disease in the Common Marmoset (Callithrix jacchus)

Abstract: Gastrointestinal disease is a frequently encountered problem among captive common marmoset (Callithrix jacchus) colonies. Management can be challenging due to the number of etiologies responsible for gastrointestinal disease in this species, limitations on diagnostic capabilities, and lack of effective treatments. Understanding commonly described GI diseases in the captive marmoset can provide insight on the impact these diseases have on research studies and aid in the development of appropriate management str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 85 publications
1
20
0
Order By: Relevance
“…Autopsy examination revealed a narrowing lumen of the distal duodenum due to an ulcer scar or abnormal flexure, suggesting an association with duodenal ulceration, duodenal-colonic adhesion, or cholangitis; however, the onset of the disease is not clear and similar cases has been found in other colonies [38]. We have established diagnosis methods for duodenal dilation using a combination of radiography and ultrasonography [38], and we will continue to investigate the etiology of the disease and treatment options. Neoplasms observed in marmosets at the CIEA included intestinal lymphomas and small intestinal adenocarcinomas, which are the commonly observed GI tumors in captive colonies [37,38,41], as well as rare lung adenocarcinomas [42].…”
Section: Research On Veterinary Management Of Marmosets At Cieamentioning
confidence: 96%
See 2 more Smart Citations
“…Autopsy examination revealed a narrowing lumen of the distal duodenum due to an ulcer scar or abnormal flexure, suggesting an association with duodenal ulceration, duodenal-colonic adhesion, or cholangitis; however, the onset of the disease is not clear and similar cases has been found in other colonies [38]. We have established diagnosis methods for duodenal dilation using a combination of radiography and ultrasonography [38], and we will continue to investigate the etiology of the disease and treatment options. Neoplasms observed in marmosets at the CIEA included intestinal lymphomas and small intestinal adenocarcinomas, which are the commonly observed GI tumors in captive colonies [37,38,41], as well as rare lung adenocarcinomas [42].…”
Section: Research On Veterinary Management Of Marmosets At Cieamentioning
confidence: 96%
“…Our clinical and pathological surveys in the past five years (2017-2021) revealed that primary spontaneous diseases in marmosets leading to death or euthanasia were marmoset wasting syndrome (MWS), followed by duodenal dilation and neoplasms. This result indicates that gastrointestinal (GI) diseases are common in captive marmosets and a major health problem for the colony [37,38]. MWS is clinically characterized by impaired weight gain, weight loss, muscle atrophy, and alopecia commonly accompanied with anemia and hypoalbuminemia [39,40].…”
Section: Research On Veterinary Management Of Marmosets At Cieamentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory bowel disease (IBD) prevalence is reported to be as high as 28–60% in captive marmosets and presents with diarrhea, weight loss, enteritis, muscle atrophy, alopecia, hypoproteinemia, anemia, elevated liver enzymes, failure to thrive and mortality 1 , 3 . In addition to IBD, a novel GI disease has been described in young adult to adult marmosets characterized by duodenal dilation or stricture near the major duodenal papilla 4 6 . Clinical signs, such as diarrhea, weight loss, or poor weight gain, resemble IBD but increased vomiting is also observed.…”
Section: Introductionmentioning
confidence: 99%
“…Histologically, duodenal mucosal ulcerations with associated chronic-active granulocytic and lympho-histiocytic inflammation were observed. Thus far only two institutions have reported this disease characterized by duodenal dilation amongst captive marmosets 6 . This duodenal syndrome was found in 21.9% of necropsy cases in a Japanese institution 4 .…”
Section: Introductionmentioning
confidence: 99%